2022
DOI: 10.1007/s12274-022-4817-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel-based composites beyond the porous architectures for electromagnetic interference shielding

Abstract: With the rapid development of the electronic industry and wireless communication technology, electromagnetic interference (EMI) or pollution has been increasingly serious. This not only severely endangers the normal operation of electronic equipment but also threatens human health. Therefore, it is urgent to develop high-performance EMI shielding materials. The advent of hydrogel-based materials has given EMI shields a novel option. Hydrogels combined with conductive functional materials have good mechanical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 122 publications
0
16
0
Order By: Relevance
“…However, the performance of EMI shielding depends on many factors, for example, conductivity of hydrogels, polarization loss capabilities, and multiple reflections of incident EMWs. Most functional materials can be easily and uniformly dispersed in hydrogels to form conductive pathways, contributing to the high conductive loss of the incident EMWs . It has already been reported that if there are enough water-rich environments along with moderate conductive properties, enhanced attenuation of penetrated waves provides absorption dominated EMI shielding performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the performance of EMI shielding depends on many factors, for example, conductivity of hydrogels, polarization loss capabilities, and multiple reflections of incident EMWs. Most functional materials can be easily and uniformly dispersed in hydrogels to form conductive pathways, contributing to the high conductive loss of the incident EMWs . It has already been reported that if there are enough water-rich environments along with moderate conductive properties, enhanced attenuation of penetrated waves provides absorption dominated EMI shielding performance.…”
Section: Resultsmentioning
confidence: 99%
“…Most functional materials can be easily and uniformly dispersed in hydrogels to form conductive pathways, contributing to the high conductive loss of the incident EMWs. 45 It has already been reported that if there are enough water-rich environments along with moderate conductive properties, enhanced attenuation of penetrated waves provides absorption dominated EMI shielding performance. The total electromagnetic shielding effectiveness (SE T ) is the sum of the shielding effectiveness due to the reflection component (SE R ), the absorption component (SE A ), and/or the internal multiple reflection component (SE M ).…”
Section: Emi Shielding Performancementioning
confidence: 99%
“…Moreover, the proposed biomimetic honeycomb microstructure greatly enhanced the reflection and dissipation of EMWs, which had been illustrated in previous reports. [ 43‐44 ] Finally, this aerogel exhibited remarkable SSE and SSE/ d up to 30660 dB·cm 3 ·g –1 and 189400 dB·cm 2 ·g –1 , respectively.…”
Section: Biopolymers For Aerogel‐based Emi Shieldsmentioning
confidence: 99%
“…Nowadays, wireless electronic equipment is in a high-speed development stage in all fields. , From the massive use of mobile phones, Wi-Fi, and 5G technologies in daily life to radars and stealth fighters in the national defense industry, electromagnetic waves (EMW) can be seen everywhere and play an irreplaceable role. , However, the widespread use of EMW has seriously affected human health and military security while benefiting mankind. Unwanted EMW has become the fourth largest source of pollution in the world, which has raised concerns about addressing the hazards of leaking electromagnetic radiation .…”
Section: Introductionmentioning
confidence: 99%